2016
DOI: 10.1002/rmv.1885
|View full text |Cite
|
Sign up to set email alerts
|

The clinical implications of hepatitis B virus genotypes and HBeAg in pediatrics

Abstract: SummaryAlthough a successful vaccine against HBV has been implemented in 184 countries, eradication of hepatitis B virus (HBV) is still not on the horizon. There are over 240 million chronic carriers of HBV globally. The risk of developing chronic hepatitis ranges from >90% in newborns of hepatitis Be antigen (HBeAg)‐positive mothers, 25%–35% in children under 5 years of age and <5% in adults. HBeAg, a non‐particulate viral protein, is a marker of HBV replication. This is the only HBV antigen to cross the plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
72
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 153 publications
(265 reference statements)
4
72
0
2
Order By: Relevance
“…This is in line with previous studies indicating that African CHB patients have a lower rate of HBeAg positivity compared to those in the Far East [21]. This phenomenon is explained, at least partly, by geographical variations in HBV genotypes and mode of transmission [22]. Indeed, over the past few decades, HBeAg negative CHB has become the commonest type of HBV infection in many countries of the world.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with previous studies indicating that African CHB patients have a lower rate of HBeAg positivity compared to those in the Far East [21]. This phenomenon is explained, at least partly, by geographical variations in HBV genotypes and mode of transmission [22]. Indeed, over the past few decades, HBeAg negative CHB has become the commonest type of HBV infection in many countries of the world.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, a recent study revealed that HBV genotypes A and D which are more efficiently transmitted by horizontal means [24] are the most predominant in Uganda [25]. Data indicate that individuals with HBV sub-genotype A1 and genotype D usually seroconvert to anti-HBe (HBeAg negative) status before their gestation age [26,27]. Thus, they are less likely to have significant ongoing HBV replication when they start conceiving.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Southeast Asia, where vertical transmission is the predominant route of disease transmission, our findings support the hypothesis that majority of HBV infections in SSA are acquired through horizontal means. Horizontal transmission of HBV can be prevented through vaccination even during the 6 week first dose inoculation [26]. It is not clear why there is a high HBV prevalence in northern Uganda but we hypothesize that it is most probably a result of using unsterile equipment for cultural practices such as scarification.…”
Section: Discussionmentioning
confidence: 99%
“…На основе различий между нуклеотидными последовательностями ВГВ подразделяют на 10 генотипов, обозначенных латинскими буквами от А до J. Генетическая вариабельность составляет 8 %. Клиническая картина заболевания зависит от генотипических особенностей ВГВ [2,3]. В Российской Федерации развитие эпидемического процесса гепатита В обусловлено циркуляцией вируса гепатита В генотипов D и А (92 и 8 % лиц соответственно) 3 .…”
unclassified
“…Клиническая картина заболевания зависит от генотипических особенностей ВГВ [2,3]. В Российской Федерации развитие эпидемического процесса гепатита В обусловлено циркуляцией вируса гепатита В генотипов D и А (92 и 8 % лиц соответственно) 3 .…”
unclassified